Going home - Mohr, Nicholasa (New York Dial Books for Young Readers, 1986)
Feeling like an outsider when she visits her relatives in Puerto Rico for the first time, eleven-year-old Felita tries to come to terms with the heritage she always took for granted.
Keywords: Puerto Ricans -- New York (State) -- New York -- Fiction; Family life -- Fiction; New York (N.Y.) -- Fiction; Puerto Rico -- Fiction